The Effectiveness of Academic Monitoring and Evaluation on Length of Study at Nusa Cendana University - HAILITIK, Ossa; DJAHA, Ajis Salim Adang; Mas’amah (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to analyze the effectiveness of academic monitoring and evaluation on student study duration at Nusa Cendana University and identify influencing factors. The background of this study is based on the phenomenon of the high number of students who do not graduate on time, which directly impacts the quality of the institution and the accreditation of study programs. Academic monitoring and evaluation are important managerial tools in controlling and accelerating student study completion. This study used a qualitative approach with a case study method. Data were obtained through in-depth interviews, participant observation, and documentation studies of the policies and implementation of academic monitoring and evaluation at Nusa Cendana University. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of academic monitoring and evaluation is not fully effective in influencing the accuracy of student study duration. Several weaknesses were identified, including minimal intensity of academic guidance, weak follow-up on evaluation results, suboptimal utilization of the academic information system, and limited intervention for students experiencing delays in their studies. Factors influencing the effectiveness of monitoring and evaluation include the capacity of the supervisor, academic management, student motivation, and institutional support. This research recommends strengthening the monitoring and evaluation system to be more systematic and responsive, increasing the role of academic advisors, and developing data-driven policies to support students in completing their studies on time.